Текстологические особенности стишного пролога ГИМ, Увар. 56 - Владимировна Чистякова, Марина (Slavistica Vilnensis, 2010)
The article is devoted to the analysis of the oldest preserved copy of the Metrical synaxarion, created and used in the Grand Duchy of Lithuania – the Russian State Museum Uvarov collection’s synaxarion No. 56-1, 1490’s, September – February. The following features are characteristic of this particular synaxarion: 1. The Metrical synaxarion of Bulgarian translation is taken as a basis; 2. Many similarities with the Novgorod redaction of the Metrical synaxarion are revealed, however, the structures are not alike (there are significant differences in the content of lives, didactic sections do not coincide, the calendar distribution of materials differs); 3. While creating the given version of the Metrical synaxarion bibliognosts turned to the Simple synaxarion. The analysis of borrowings makes it possible to conclude that the compilers used both short and expanded redactions. 4. It is most likely that the short redaction has been used while compiling didactic sections, whereas some of the lives were most obviously oriented towards the expanded redaction; 5. Some life texts are compiled by merging and combining the materials of the Simple and Metrical synaxaria; 6. The life section is enriched by texts that are new to the Metrical synaxarion, such as the lives of St. Peter and Alexius, Metropolitans of Moscow, the cycle of 10 lives of the Kievan Caves Monastery monks; 7. A small number of new didactic readings are included (3 sermons, 2 stories about the miracles of the saints). The revealed textological features allow to state that we are dealing with a special redaction of the Metrical synaxarion, the content of which differs from those of Tymovo, Lucius, Barlaam, Moscow and Novgorod, as distinguished by G. Petkov. Given redaction was widespread in the Grand Duchy of Lithuania, at the moment 13 copies (autumn and spring half of the year) of similar content are known of.